IbM Optimalisasi Kinerja Kelompok Posyandu Jurusan Kebidanan Kabupaten Banyuasin - Murdiningsih, Murdiningsih; Rohaya, Rohaya; Sumastri, Heni (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2019)
Posyandu is a forum for health service activities from, by and for the community, with the aim of bringing basic and other health services needed by the community directly to individuals, groups, families. The success of Posyandu management requires strong support from various parties, both moral, material and financial support. In addition, collaboration with various related sectors is needed. In addition, the persistence and dedication of managers and cadres all have strategic roles in supporting the success of Posyandu implementation. Based on field data/situation analysis, Kenten Laut village is a village located on the outskirts of the city in Talang Kelapa District, Banyuasin Regency. Has 3 posyandu, the number of cadres is 15 people, the number of toddlers is 27.17%, the coverage of toddlers at the posyandu is 45.16%, KMS ownership is 0%, home visits have not been carried out, the education level of cadres is low (66.67%), books/administration Posyandu is not complete, Reporting is not going well. Social analysis shows that the knowledge and skills of cadres in carrying out their duties are still far from expectations, this can be seen from the implementation of the five service steps on the D day or the day when the posyandu is still running modestly/inadequately, and home visits have never been carried out by cadres. In connection with these conditions, mentoring, coaching and home visits have been carried out (10 October & 10 November 2016 at the Melati Posyandu, on 12 October and 12 November 2016 at the Red Orchid Posyandu, an evaluation of the results of mentoring and coaching as well as a home visit on opening day has been carried out Posyandu there is progress / improvement in both the quality of service and the caverage of posyandu visitors. The results of the evaluation showed that there was a significant increase in knowledge and skills in carrying out activities in each step of the five steps of the posyandu, the provision of PMT was in accordance with the recommended menu, home visits had been carried out by cadres. Suggestions still need to be continued with assistance and guidance in the field of administration and increasing community participation (PSM). So that the presence of posyandu strata can be increased to become Plenary/Independent Posyandu.